ANALYSIS OF VIOLATIONS OF THE OFFICE OF A NOTARY AS AN ADVOCATE BASED ON A SHARIA PERSPECTIVE - Adriansyah, Muhammad; Jefri Kurniawan, Muhammad (Jurnal Impresi Indonesia, 2023)
A notary is a public official with the authority to do authentic deeds. In Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notaries, article 17 paragraph (1) states that Notaries are prohibited from holding the same position as Advocates. However, there have been cases of notaries holding concurrent positions as advocates. This research further examines violations of notaries who hold concurrent positions as advocates based on a sharia perspective. This research uses a normative juridical research method. The data used in this research is secondary data. Secondary data includes primary legal materials and secondary legal materials. The primary material used is regulations, while the secondary material used is literature related to this research. In this research, the author used qualitative data analysis to produce descriptive data. Based on the research results, notaries cannot violate the established code of ethics in their positions. This is because if a notary violates the professional code of ethics, it means that the Notary is violating the oath in Islam called the karat oath. Violations of the Code of Ethics for Notaries with Multiple Positions in the view of Islamic law are prohibited to avoid conflicts of interest or conflicts of interest. In the Islamic religion, it is also said that every profession must be carried out diligently (Putin). The prohibition on holding multiple positions for notaries also aligns with independence (al-istiqlaliyah) in the legal field. This independence can only be captured in other professions within the notary public. Apart from that, this is also in line with the principle of professionalism, in which the concept of Sharia is referred to as al-qowiy.